Nitrogen fertilizer rate but not form affects the severity of Fusarium wilt in banana - Orr, Ryan; Dennis, Paul G.; Wong, Yide; Browne, Daniel J.; Cooper, Martha; Birt, Henry W. G.; Lapis-Gaza, Hazel R.; Pattison, Anthony B.; Nelson, Paul N. (Frontiers in Plant Science, 2022)
Nitrogen (N) fertilisers are routinely applied to bananas (Musa spp.) to increase production, but may exacerbate plant diseases like Fusarium wilt of banana (FWB) - the most economically important disease of banana. Here, we characterised the effects of N rate and form (ammonium or nitrate) on plant growth, FWB severity, the banana root proteome, the concentration of Fusarium oxysporum f.sp. cubense (Foc) (the causal agent of FWB), and the diversity of rhizosphere bacterial and fungal communities. Banana plants (Musa ABB) were grown under greenhouse conditions in soil with ammonium or nitrate supplemented at five N rates, and with or without inoculation with Foc. The growth of non-inoculated plants was positively correlated with N rate. In bananas inoculated with Foc, disease severity increased with N rate, resulting in Foc-inoculated plant growth being greatest at intermediate N rates. The abundance of Foc in the soil was weakly related to the treatment conditions and was a poor predictor of disease severity. Fungal diversity was consistently affected by Foc inoculation, while bacterial diversity was associated with changes in soil pH resulting from N addition, in particular ammonium. N rate altered the expression of host metabolic pathways associated with carbon fixation, energy usage, amino acid metabolism, and importantly stress response signalling, irrespective of inoculation or N form. Furthermore, in diseased plants, Pathogenesis-related protein 1, a key endpoint for biotic stress response and the salicylic acid defence response to biotrophic pathogens, was negatively correlated with the rate of ammonium fertiliser but not nitrate. As expected, inoculation with Foc altered the expression of a wide range of processes in the banana plant including those of defence and growth. In summary, our results indicate that the severity of FWB was negatively associated with host defences, which were influenced by N application (particularly ammonium), and shifts in microbial communities associated with ammonium-induced acidification.